The Influence Of Prospective Political Marketing On The Political Behavior Of Voters In Simultaneous Village Head Elections in Kahu District, Indonesia - Ekapurnama, Fifin; Hawing, Hardianto; Hamrun, Hamrun; Alim, Irwan (Journal of Contemporary Local Politics, 2022)
The purpose of this study was to determine the effect of Political Marketing of Candidates on Voter Political Behavior in Simultaneous Village Head Elections in Kahu District, Bone Regency in 2021. Voting behavior is influenced by several factors, one of which is political marketing. Good and targeted political marketing can increase voting behavior. This study uses descriptive quantitative and associative research methods, using a questionnaire instrument. The technique of placing the sample in this study is random sampling. The target is the community/voters in Bonto Padang Village, Kahu District, Bone Regency with the number of samples used as many as 91 people. Data collection techniques used are observation, questionnaires and documentation. The data analysis technique used simple linear regression analysis. Validity data obtained through validity and reliability tests. The results of this study indicate that political marketing of candidates has an influence on the political behavior of voters in simultaneous village head elections in Kahu District, Bone Regency. Based on the output of the summary model, the results obtained are R of 0.541 from the large influence of the independent variable or political marketing (X) on the dependent variable or voting behavior (Y) which is also strengthened by the coefficient of determination (R Square) or the determinant coefficient of 0.293 which means 29,3%